Pore scale evaluation of thermal conduction anisotropy in granular porous media using Lattice Boltzmann method. Issue 4 (3rd April 2017) - Askari, R.; Ikram, M.F.; Hejazi, S. H.
Abstract : Purpose: Thermal conduction anisotropy, which is defined by the dependency of thermal conductivity on direction, is an important parameter in many engineering and research studies such as the design of nuclear waste depositional sites. In this context, the authors aim to investigate the effect of grain shape in thermal conduction anisotropy using pore scale modeling that utilizes real shapes of grains, pores and throats to characterize petrophysical properties of a porous medium. Design/methodology/approach: The authors generalize the swelling circle approach to generate porous media composed of randomly arranged but regularly oriented elliptical grains at various grain ratios and porosities. Unlike previous studies that use fitting parameters to capture the effect of grain–grain thermal contact resistance, the authors apply roughness to grains' surface. The authors utilize Lattice Boltzmann method to solve steady state heat conduction through medium. Findings: Based on the results, when the temperature field is not parallel to either major or minor axes of grains, the overall heat flux vector makes a "deviation angle" with the temperature field. Deviation angle increases by augmenting the ratio of thermal conductivities of solid to fluid and the aspect ratios of grains. In addition, the authors show that porosity and surface roughness can considerably change the anisotropic properties of a porous medium whose grains are elliptical in shape. Originality/value: The authors developed an algorithm for generation of non-circular-based porous medium with a novel approach to include grain surface roughness. In previous studies, the effect of grain contacts has been simulated using fitting parameters, whereas in this work, the authors impose the roughness based on the its fractal geometry.